SZ_GERICHTE BEK 2016 190 vom 11. April 2017 , Nichtanhandnahme (Diebstahl, Art. 139 StGB; Lok 205) - SZ Gerichte (2017)
Nichtanhandnahme (Diebstahl, Art. 139 StGB; Lok 205) | Nichtanhandnahme Strafverfahren